Persepsi Generasi Millineal terhadap Jilbab sebagai Identitas, Fesyen, Komunikasi Nonverbal dan Kreativitas - Poerwanto Poerwanto; Reza Praditya Yudha (Diploma Travel Business, Faculty of Social and Political Science, Jember University, 2019)
Abstract This research aimed to describe millenial generation perception of viel as identity, fashion, communication, and creativity. It used the focus discussion group technique. The result showed a variety of viel perception. As an identity, viel became moslemah wearing that must be according to Islamic rules. Viel also could be used in various daily activities as long as it didn’t disturbed the activity’s purpose. In its development, viel has been a chiq wearing and has been included to the fashion sphere. Fashion and creativity were a sphere to express the ability in the dynamic of modelling and business world. Viel as an identity and fashion gave a vast chances and challenges for the designers and businessmen to create creative modes gradually. The main challenge for the fashion designer and businessmen were because viel was originally derived from moslem fashion tied by Islamic rule. Veil (jilbab) are identity, fashion, nonverbal communication and creativity. Keywords: Millenial generation, Hijab, Identity